2020
DOI: 10.1007/jhep06(2020)113
|View full text |Cite
|
Sign up to set email alerts
|

Conformal symmetry and composite operators in the O(N )3 tensor field theory

Abstract: We continue the study of the bosonic O(N) 3 model with quartic interactions and long-range propagator. The symmetry group allows for three distinct invariant φ 4 composite operators, known as tetrahedron, pillow and double-trace. As shown in [1, 2], the tetrahedron operator is exactly marginal in the large-N limit and for a purely imaginary tetrahedron coupling a line of real infrared fixed points (parametrized by the absolute value of the tetrahedron coupling) is found for the other two couplings. These fixed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 76 publications
(180 reference statements)
0
28
0
Order By: Relevance
“…Fishnet diagrams are very different from melonic diagrams in general. Nonetheless, as noticed in [73], the fishnet model has a number of similarities with the long-range O(N ) 3 model. For example, while melonic diagrams characteristically show up in the two-point function, there are no planar fishnet diagrams for the two-point function; however, for d < 4 the long-range nature of the kinetic term makes such difference irrelevant from the renormalization point of view, as there is no wave function renormalization in any case.…”
Section: Jhep05(2021)004mentioning
confidence: 80%
See 2 more Smart Citations
“…Fishnet diagrams are very different from melonic diagrams in general. Nonetheless, as noticed in [73], the fishnet model has a number of similarities with the long-range O(N ) 3 model. For example, while melonic diagrams characteristically show up in the two-point function, there are no planar fishnet diagrams for the two-point function; however, for d < 4 the long-range nature of the kinetic term makes such difference irrelevant from the renormalization point of view, as there is no wave function renormalization in any case.…”
Section: Jhep05(2021)004mentioning
confidence: 80%
“…It is more convenient to illustrate the instability in long-range models. The long-range quartic O(N ) 3 model has been introduce and studied in [14,62,73,74] (see also [75] for a review).…”
Section: O(n ) 3 Tensor Model With Quartic or Higher Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, explicit calculations in the cubic O(N ) model of [44,45] have shown that indeed imaginary parts of scaling dimensions are (exponentially) suppressed at large N [58]. Moreover, along the lines of long-range O(N ) 3 tensor model [19][20][21][22], we will introduce and study also a long-range version of the AR model, for which the coupling is exactly marginal at large N , and we will find that in this case a real and unitary CFT can be identified at small coupling for either real or imaginary coupling, even at integer dimensions d < 6.…”
Section: Jhep04(2021)197mentioning
confidence: 99%
“…It is of course still possible to study SYK-like models in more than one dimension [8][9][10], but tensor models have some more appealing features, in particular in view of a potential AdS/CFT correspondence, such as the fact that they have a global symmetry from the start, which could then be gauged, whereas in SYK-like models the symmetry only emerges after quenching. As a consequence several tensor models have been studied, with a focus on the fact that their melonic large-N limit allows the identification of non-trivial fixed points of the renormalization group and the non-perturbative computation of the spectrum of bilinear operators [7,[11][12][13][14][15][16][17][18][19][20][21][22] (see also [23][24][25][26] for reviews and more references).…”
Section: Introductionmentioning
confidence: 99%